The Influence Of Service Quality On Community Satisfaction At The Religious Affairs Office Of East Banggae District, Majene District - Hurul Aini Dzulqaidah; Zalkha Soraya; Muahmmad Akib (International Journal of Economic Research and Financial Accounting, 2024)
This research aims to determine the effect of service quality on community satisfaction at the Religious Affairs Office (KUA) East Banggae District, Majene Regency. This study uses a quantitative approach. The subjects of this research were people who had interests in the East Banggae District Religious Affairs Office and a sample of 88 people was taken. The data collection method uses a questionnaire. The data analysis technique used is Simple Regression Analysis using statistical calculations via the Statistical Package for the Social Science (SPSS) application. The research results show that Service Quality (X) has a positive and significant effect on community satisfaction (Y), seen from the results of the calculated t value > t table (8.760 > 1.662) and the significant value (0,01 < 0.05).